The trouble with numbers: Some fundamental flaws with using standardised outcome measures. (4th October 2017) - Rodgers, Brian
Abstract: The modern paradigm of evidence‐based practice dominates the therapeutic world and influences all aspects of the profession. Yet this pervasive concept is based on surprisingly shaky ground. When looked at in detail, the source of the raw data used as the basis of much of this evidence, standardised outcome measures, can be seen to be fundamentally flawed. This article sets out the many methodological, sociopolitical, and technical flaws in standardised outcome measures, and asks what this means for the field of psychotherapy.